MOTIVASI BELAJAR WARGA BINAAN DALAM MENGIKUTI PENDIDIKAN KESETARAAN DI PKBM BINA LAPASKAS CENTER: STUDI KASUS LAPAS KELAS III RANGKASBITUNG - Destia Pratiwi; M. Syadeli Hanafi; Ahmad Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to (1) identify the learning motivation of inmates in participating in equivalency education at PKBM Bina Lapaskas Center in Class III Rangkasbitung Correctional Facility, and (2) examine the factors influencing inmates’ learning motivation in the program. The method used in this research is a descriptive method with a qualitative approach through a case study.The data sources consist of primary and secondary data. Primary data were obtained through in-depth interviews and direct observation involving 15 informants, including inmates participating in Package A, B, and C programs, equivalency education tutors, and the management of PKBM Bina Lapaskas Center. Meanwhile, secondary data were collected from PKBM administrative documents, inmate attendance records, learning activity reports, inmates’ certificates, as well as relevant books and journal articles. The data analysis technique was carried out through data reduction, data display, and conclusion drawing. The results of this study indicate that (1) the learning motivation of inmates in participating in equivalency education is still not optimal, as reflected in several indicators such as inconsistent attendance, varying levels of activeness in the learning process, uneven seriousness in completing assignments, and participation in educational activities that still needs to be improved. (2) the factors influencing learning motivation consist of internal and external factors. Internal factors include the desire to improve oneself, future expectations, as well as varying levels of interest and learning awareness among individuals. External factors include tutor support, learning methods, the learning environment within the correctional facility, and limited learning facilities, all of which affect inmates’ involvement in the learning process.